2019
DOI: 10.2302/kjm.2019-0003-oa
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells: Pathophysiological Roles and Clinical Applications

Abstract: Inflammation and immune responses after tissue injury play pivotal roles in the resolution of inflammation, tissue recovery, fibrosis, and remodeling. Regulatory T cells (Tregs) are responsible for immune tolerance and are usually activated in secondary lymphatic tissues. Activated Tregs subsequently regulate effector T cell and dendritic cell activation. For clinical applications such as the suppression of both autoimmune diseases and the rejection of transplanted organs, methods to generate stabilized antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 141 publications
(159 reference statements)
0
11
0
Order By: Relevance
“…Methylation of the foxp3 gene has an essential role in transcription of the gene, which further translates to cell phenotype and activity [68] . We thus evaluated the methylation status of the six regulatory regions of the foxp3 gene in FACS-sorted CD4 + FoxP3 + cells ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Methylation of the foxp3 gene has an essential role in transcription of the gene, which further translates to cell phenotype and activity [68] . We thus evaluated the methylation status of the six regulatory regions of the foxp3 gene in FACS-sorted CD4 + FoxP3 + cells ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…16 Tregs may proliferate on the ischemic hemisphere side 7 days after tMCAO, indicating a possible kinetic delay in the adaptive immune response. 16,18,19 The increase of brain Tregs was significantly higher in aged male mice than in females at 15 days after tMCAO, indicating that the immune response of brain T cells may be time-specific and gender-specific. 20 In contrast to these findings, Kleinschnitz et al found a marked increase of Foxp3 + Tregs in the brain within 24 hours after tMCAO, but predominantly in the cerebral vasculature.…”
Section: Changes In the Number Of Tregs In The Brain After Ischemic Strokementioning
confidence: 98%
“…On day 14 after stroke, 40% of CD4 + T cells were Foxp3 + Tregs, which were recruited in and around the infarct area, and their number persistently increased and remained at a high level for 2 months 16 . Tregs may proliferate on the ischemic hemisphere side 7 days after tMCAO, indicating a possible kinetic delay in the adaptive immune response 16,18,19 . The increase of brain Tregs was significantly higher in aged male mice than in females at 15 days after tMCAO, indicating that the immune response of brain T cells may be time‐specific and gender‐specific 20 .…”
Section: Dynamic Changes Of Tregs In Various Stages Of Experimental Ischemic Strokementioning
confidence: 99%
See 2 more Smart Citations